Accuracy assessment of integrated GNSS measurements with LIDAR mobile mapping data in urban environments. (December 2021) - Paijitprapaporn, Chanachon; Thongtan, Thayathip; Satirapod, Chalermchon
Abstract: Global Navigation Satellite System (GNSS) is space-based systems for positioning, navigation and timing. Non-GNSS sources are aiding to maintain accuracy of system states including positioning, velocity, acceleration, attitude and angular rate essential in applications involving reliable and accurate real-time navigation solutions, safety-of-life systems and control of trajectory. Although GNSS capabilities are rapidly increased, challenges still exist when GNSS signals are not available and spoofing is mitigated; therefore, integrated information from different sources including GNSS, Inertial Navigation System (INS), Distance Measuring Instrument (DMI) and Terrestrial Laser Scanner (TLS) are required to maintain system state or improve navigation system performances. This paper presents integration information from GNSS and various sources available in a terrestrial light detection and ranging (LIDAR) mobile mapping system where a tight coupled system; in observation domain, is formulated and various GNSS measurements are applied to access its positioning accuracy in urban scenes throughout the advantages, disadvantages and trade-offs.